2020
DOI: 10.18178/ijmlc.2020.10.1.904
|View full text |Cite
|
Sign up to set email alerts
|

Modified Selection Sort Algorithm Employing Boolean and Distinct Function in a Bidirectional Enhanced Selection Technique

Abstract: A sorting algorithm is a step by step procedure in arranging items on the list in particular order (ascending or descending). Sorting is one of the important data structure concepts that play a vital role in computer systems, file management, memory management, and many real-life applications. Among the sort algorithm, selection sort is the simplest and very straightforward. However, selection sort is considered the second worst algorithm concerning time complexity for large data. Due to the lousy performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In their research, Vilchez tried to reduce the number of comparisons and iterations that usually causes the delay in terms of sorting. The results showed that the modified algorithm has a significant run time complexity improvement compared with other O(n 2 ) algorithms (Vilchez, 2020). The sorting algorithm must be effective, less complex, stable, and more efficient.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…In their research, Vilchez tried to reduce the number of comparisons and iterations that usually causes the delay in terms of sorting. The results showed that the modified algorithm has a significant run time complexity improvement compared with other O(n 2 ) algorithms (Vilchez, 2020). The sorting algorithm must be effective, less complex, stable, and more efficient.…”
Section: Literature Reviewmentioning
confidence: 98%
“…They could validate running time complexity. Their research results showed that the newly created selection sort algorithm by using distinct and boolean function in the technique of a bidirectional enhance selection has a significant improvement in terms of run time complexity compared with other sorting algorithms (Vilchez, 2020). Alotaibi proposed a new in-place sorting algorithm called OneByOne (OBO) sort.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation